The influence of different forms of black cumin (Nigella sativa L.) on the characteristics of sheep’s curd cheese - Voșgan, Zorica; Dumuța, Anca; Mihali, Cristina; Dippong, Thomas; Mihalescu, Lucia; Marian, Monica; Mihalescu, Beatrice (Frontiers in Sustainable Food Systems, 2024)
The influence of different forms of Nigella sativa (seeds, powder, alcoholic extract, oil) on the traditional sheep curd was investigated by comparison with a control simple curd considering a series of sensorial, physical-chemical, and microbiological aspects. The analysis was performed on curds freshly prepared and after 10 days of refrigeration. The sensory analysis of the curds was performed using a variety of methods such as scaling method, the method of quality describing, the method of ordering by rank, "triangle" method and "duo-trio" method. The analysed curds were assessed and classified according to their sensory characteristics and to their typicality. The N. sativa supplementing of the sheep curds improved their physical-chemical characteristics by raising the fat content with 0.88-2.82% and decreasing the titratable acidity with 1.42-2.32 % compared to the control curd without additive. After 10 days of refrigeration the titratable acidity increased with 1,58-3,25 % and moisture decreased (8.43-13.17%). The microbiological quality of the curd samples was influenced by the addition of black cumin in different forms, with variations in the total number of bacteria (TNB) between 4.33-4.39 log CFU/g compared to the control sample 5.03 log CFU/ g, Enterobacteriaceae (2.53-2.58 log CFU/g) compared to the control sample 2.60 log CFU/g and coagulase-positive staphylococci (CPS) 2.30-2.68 log CFU/g compared to the control sample 2.75 log CFU/g. After 10 days of refrigeration, the number of microorganisms decreased, TNB (4.13-4.31 log CFU/g), Enterobacteriaceae (2.34-2.53 log CFU/g) and CPS (2.02-2.55 log CFU/g), while for the control sample the values increased. The most obvious antimicrobial effect was observed in the case of the cold-pressed oil addition (1%), followed by the alcoholic extract (1%), seeds (3%) and powder (3%).